Gloss on the judgement of the Supreme Administrative Court of 21 October 2022, III OSK 4468/21 (concerning the provision of public information by a foundation) (Ius Novum, 2024)
In its judgment of 21 October 2022, III OSK 4468/21, the Supreme Administrative Court considered that a foundation is obliged to provide public information because, in accordance with Article 1 of the Act on Foundations, it should accomplish socially and economically useful objectives that comply with the interests of the Republic of Poland. These are objectives that should also be accomplished by public administration; thus, they are, in fact, the State’s objectives. In such a situation, the Court decided that the informative obligation of foundations that are not public law entities applies, in fact, to every aspect of their activities. This shouldbe recognised as correct, because the constitution-maker specified in Article 61(1) of the Constitution of the Republic of Poland a very broad range of entities obliged to provide public information, ensuring that every field of the State’s activity is transparent.